2021
DOI: 10.3892/etm.2021.11038
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of using plasma long non‑coding RNAs ANRIL and HOXA11‑AS for in‑stent restenosis

Abstract: In-stent restenosis (ISR) can pose serious challenges for cardiologists following coronary stent implantation. Early identification of patients at high risk of ISR is considered to be effective for its prevention. However, factors that can reliably predict the risk of ISR remain elusive at present. The present study aimed to investigate the possible association between plasma long non-coding RNA (lncRNA) levels and ISR. A total of 410 patients with single-vessel lesion who received drug-eluting stents (DES) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…High ANRIL expression was considered as an independent risk factor for in-stent restenosis. However, it was declared that the added diagnostic potential of ANRIL will be reached when combined with expression level of other lncRNAs like homeobox A11 antisense [ 115 ].…”
Section: Anril Functionsmentioning
confidence: 99%
“…High ANRIL expression was considered as an independent risk factor for in-stent restenosis. However, it was declared that the added diagnostic potential of ANRIL will be reached when combined with expression level of other lncRNAs like homeobox A11 antisense [ 115 ].…”
Section: Anril Functionsmentioning
confidence: 99%
“…Furthermore, another study indicated that the expression of HOTAIR is significantly downregulated with chronic HF ( 89 ). Finally, HOXA11-AS expression is downregulated in the plasma of patients with in-stent restenosis (ISR) compared to that in patients without ISR, and it was found to be an independent protective factor for ISR ( 90 ). In summary, the large amounts of data presented provide evidence for the use of HOX-lncRNAs as diagnostic markers of cardiovascular diseases, and future in-depth studies of these markers are expected to contribute to their use as potential therapeutic targets.…”
Section: Hox-lncrnas As Potential Diagnostic Biomarkers For Cardiovas...mentioning
confidence: 99%